2020
DOI: 10.3233/ves-190683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term vestibular rehabilitation therapy with vibrotactile sensory augmentation for people with unilateral vestibular disorders – A randomized preliminary study

Abstract: BACKGROUND AND OBJECTIVE: This pilot study aimed to investigate the effects of incorporating vibrotactile sensory augmentation (SA) on balance performance among people with unilateral vestibular disorders (UVD). METHODS: Eight participants with UVD were recruited. Participants completed 18 balance training sessions across six weeks in a clinical setting. Four participants (68.1 ± 7.5 yrs) were randomized to the experimental group (EG) and received trunk-based vibrotactile SA while performing the balance exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 62 publications
1
56
3
1
Order By: Relevance
“…Although a carry-over effect was seen up to 2 months post training, the effect was not as strong as the feedback effect (see Tables 3 and 4). Our carry-over effect is less pronounced than that observed by Bao et al [42] in their pilot study on vestibular loss patients, and more pronounced than that observed in other pilot studies on the elderly and patients with uncompensated unilateral vestibular loss [16]. In the study of Bao et al [42] patients received a more intense and longer training protocol -3 sessions a week for 8 weekswhich may have influenced the carry-over effect.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Although a carry-over effect was seen up to 2 months post training, the effect was not as strong as the feedback effect (see Tables 3 and 4). Our carry-over effect is less pronounced than that observed by Bao et al [42] in their pilot study on vestibular loss patients, and more pronounced than that observed in other pilot studies on the elderly and patients with uncompensated unilateral vestibular loss [16]. In the study of Bao et al [42] patients received a more intense and longer training protocol -3 sessions a week for 8 weekswhich may have influenced the carry-over effect.…”
Section: Discussioncontrasting
confidence: 52%
“…Our carry-over effect is less pronounced than that observed by Bao et al [42] in their pilot study on vestibular loss patients, and more pronounced than that observed in other pilot studies on the elderly and patients with uncompensated unilateral vestibular loss [16]. In the study of Bao et al [42] patients received a more intense and longer training protocol -3 sessions a week for 8 weekswhich may have influenced the carry-over effect. In another study of carry-over effects, Brugnera et al [48] showed a more significant improvement in the medium term carry-over effect for condition 6 (eyes closed on a sway-referenced platform) of the Equitest system which is an easier but comparable to the task standing eyes closed on foam task used in the current study [49].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The proposed methods were compared with previously developed methods with respect to the results listed in Table 5 . SVMs, random forest models, and cohorts have been applied to detect motor [ 48 , 49 ], balance, or gait function [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The highest accuracy in classifying motor function was 97%, achieved by an SVM.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with balance deficits including a diagnosed vestibular disorder or peripheral neuropathy were recruited by PTs and via flyers at the university medical center. Participants were excluded if they had confounding neurologic or neuromuscular disorders; known pregnancy; recent lower extremity fractures/severe sprains (within the last six months); previous lower extremity joint replacement; incapacitating back or lower extremity pain; the inability to stand for three minutes without rest; a body habitus that exceeded the dimensions of the measuring equipment (waist circumference >50 inches); or a Montreal Cognitive Assessment score of less than 26 points [36]. All participants gave written informed consent, and the study was conducted in accordance with the Declaration of Helsinki.…”
Section: A Datamentioning
confidence: 99%